Appliance of machine learning algorithm in the pharmaceutical sector: a review (Research, Society and Development, 2021)
The pharmaceutical industry with all of its importance has been innovating and revolutionizing in the course of the time. The information technology on its segments has a crucial role so the changes can happen, and this project will show the growth situation of the pharmaceutical industry and the importance of its technology in Brazil, in the world and also the use of algorithm as essentials tools in several areas in the pharmaceutical field. During the course of this project, to its end, will be described details showing how is the industry’s outlook, pharmaceutical technologies, algorithms being important keys at problem solving, partnerships between industries, innovations for medications, medical services and treatments. This is an integrative literature review using the Google Scholar, PubMed, Scielo and Science Direct platforms to search for articles from 2003 to 2021 on the application of machine learning algorithms in the pharmaceutical area. The use of algorithms proved to be effective, facilitating the development of new drugs and in solving existing problems.